Congenital erythropoietic porphyria linked to GATA1‐R216W mutation: challenges for diagnosis. (25th October 2014) - Di Pierro, Elena; Russo, Roberta; Karakas, Zeynep; Brancaleoni, Valentina; Gambale, Antonella; Kurt, Ismail; Winter, S. Stuart; Granata, Francesca; Czuchlewski, David Rodriguez; Langella, Concetta; Iolascon, Achille; Cappellini, Maria Domenica
Abstract Congenital erythropoietic porphyria (CEP) is a rare genetic disease that is characterized by a severe cutaneous photosensitivity causing unrecoverable deformities, chronic hemolytic anemia requiring blood transfusion program, and by fatal systemic complications. A correct and early diagnosis is required to develop a management plan that is appropriate to the patient's needs. Recently only one case of X‐linked CEP had been reported, describing the trans‐acting GATA1‐R216W mutation. Here, we have characterized two novel X‐linked CEP patients, both with misleading hematological phenotypes that include dyserythropoietic anemia, thrombocytopenia, and hereditary persistence of fetal hemoglobin. We compare the previously reported case to ours and propose a diagnostic paradigm for this variant of CEP. Finally, a correlation between phenotype variability and the presence of modifier mutations in loci related to disease‐causing gene is described.